Pulp and paper properties of soda-AQ pulping on Musa acuminata var truncate and Musa paradisiaca spp. - Lanika, Lakarim; Alazmi, Mohd Ridwan; Razali, Norhaslida; Low, Joo Choo; Idris, Muhamad Danial; Halis, Rasmina; Mohd Salleh, Naimah; Shafie, Amran (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The increasing demand for pulp and paper products has resulted in high pulping material demand. Banana pseudo-stem is a relatively new alternative material for the pulp and paper industry. The study compares two banana species, Musa acuminata var trunscata and Musa paradisiaca spp., on their pulp and papermaking properties and the effectiveness of anthraquinone (AQ) addition in the soda pulping process. Banana pseudo-stem were chipped and cooked at 14 % active alkali using different AQ additions (0.5, 0.75, and 1.0 %). AQ improved the pulp and paper properties. Between the two, M. acuminata has better pulp and paper properties than M. paradisiaca spp. The 1.0 % AQ addition resulted in the highest pulp yield but had lower paper properties compared to 0.5 and 0.75 %. Overall, the best AQ addition was 0.75 % which produced intermediate pulp yield and the highest quality in paper properties.